The Ambiguity Imperative: "Success" in a Maternal Health Program in Uganda. Issue 5 (4th July 2021) - Lange, Isabelle L.; Nalwadda, Christine Kayemba; Kiguli, Juliet; Penn-Kekana, Loveday
ABSTRACT: Global health programs are compelled to demonstrate impact on their target populations. We study an example of social franchising – a popular healthcare delivery model in low/middle-income countries – in the Ugandan private maternal health sector. The discrepancies between the program's official profile and its actual operation reveal the franchise responded to its beneficiaries, but in a way incoherent with typical evidence production on social franchises, which privileges simple narratives blurring the details of program enactment. Building on concepts of not-knowing and the production of success, we consider the implications of an imperative to maintain ambiguity in global health programming and academia.